AKTUALISASI DIRI UNTUK MENGURANGI PERILAKU BULLYING PADA ANAK - Ari Susandi Susandi; Reza Hilmy Luayyin; Aries Dirgayunita (Jurnal Visi Ilmu Pendidikan, 2022)
The research method used is descriptive qualitative analysis by presenting research updates and analysis of various opinions in scientific articles that are already in journals. Qualitative research is often described as research that publishes social phenomena and behavior as they exist (in natural setting) and is also appropriate. with facts and implemented in depth, in this case the researcher looks for existing information through journals and also existing online media then it is understood and after that then gets data and information to be added and reviewed through small notes then becomes an existing analysis so that a study that is relevant and accurate. The population and sample used in this study were 30 students consisting of class IV to class VI in the Permata Integrated Elementary School, Probolinggo City and also those from various different backgrounds. The data collection instrument is using a questionnaire in the form of google form which is sent to each student with various types of relevant questions as well as field observations in the form of open interviews during a visit to the student's probolinggo.                                           Keywords: Self-actualization, Bullying, Elementary School